Lipid Peroxidation, Immunity and Milk Yield in DL-a-Tocopheryl Acetate Supplemented Periparturient Cows During Summer and Winter - Chandra, Gulab; Aggarwal, Anjali; Kumar, Muneendra (Indian Journal of Animal Nutrition, 2017)
This study was conducted to find out the effect of DL-a-tocopheryl acetate supplementation on lipid peroxidation, immunity and milk production in periparturient cows during summer and winter seasons. Twenty four pregnant dry periparturient crossbred cows were selected, 12 each during summer and winter seasons.Selected cows were randomly assigned to two groups of six each during summer and winter. Feeding regimen was same in all the groups except that vitamin E was supplemented (1000 IU DL-a-tocopheryl acetate) from day 60 pre-partum to day of calving in experimental animals. Blood samples were collected on days -20, -10, -5, 0, 5, 10 and 20 with respect to day of parturition. Body condition score reduction and plasma thiobarbituric acid reactive substance concentration was higher (P